PERLUNYA PELATIHAN RNP PROCEDURE BAGI AIR TRAFFIC CONTROLLER (ATC) TERHADAP KESELAMATAN PENERBANGAN DI PERUM LPPNPI CABANG KENDARI - Muhammad Ari Rahman; Meita Maharani Sukma; Hari Fitrianto (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
This study aims to determine the need for RNP procedure training for ATC at Perum LPPNPI, Kendari Branch. In accordance with the Regulation of the Minister of Transportation Number PM 1 of 2014 namely the Civil Aviation Safety Regulation part 69 (PKPS part 69) regarding the License, Rating, Training and Authority of Aviation Navigation Personnel, an ATC must first receive training before using or implementing a certain flight navigation procedure. , so that to apply the RNP Procedure that has been listed in the AIP Indonesia must follow and have a training certificate for the RNP Procedure. the research method used is a qualitative method. In addition, the data collection method used in this study is the method of observation and interviews as a means of collecting data at Haluoleo Kendari Airport. Based on the results of the study, it can be concluded that the ATC personnel at Perum LPPNPI Kendari Branch agreed to obtain an RNP Procedure training certificate and could apply the RNP Procedure contained in the Kendari AIP to the maximum because the RNP procedure was needed when the main approach tool was in repair.